Comparison of the lower genital tract microbiome composition in patients with benign gynecological disease - Yonghui Shi; Jun Li; Jinjing Xie; Tianye Yang; Qiongyan Ma; Hua Chen; Wenwei Guo (Frontiers in Global Women's Health)
ObjectiveLower genital tract microbiome dysbiosis has been associated with several gynecological diseases. However, the differences in microbiome composition among patients with several gynecological diseases, such as endometrial polyps and uterine myoma, are poorly understood. Studying the lower genital tract microbiome composition in patients with benign gynecological diseases could provide new insights for interpreting the complex interplay between the microbiome and pathogenesis and finding new targets for preventive measures.MethodsA total of 16 patients with endometrial polyps (EPs), 11 patients with uterine myoma (UM), 6 patients with ovarian cysts (OC) and 36 healthy women (HWs) were recruited for this study. Samples were obtained from vaginal secretions. The DNA was isolated from the samples, and the V3-V4 regions were amplified. The sequencing libraries were generated and sequenced on an Illumina NovaSeq 6000 platform.ResultsFirmicutes, Actinobacteria and Bacteroidota were the most common phyla in all four groups, whereas OC presented the highest abundance of Firmicutes and the lowest abundance of Bacteroidota. At the genus level, Lactobacillus in the OC group was significantly greater than that in the HW group, and Atopobium in the UM group was significantly lower than that in the HW group. The abundance of Gardnerella was greater in the UM group than in the EP group, and the abundance of Streptococcus was greater in the EP group. The richness and evenness of the microbiome were generally consistent among the HW, EP, UM, and OC groups. Principal component analysis (PCA), principal coordinate analysis (PCoA) and nonmetric multidimensional scaling (NMDS) revealed no distinct separation trends among the four groups. According to ANOSIM, there was no significant difference in community structure among the four groups.ConclusionsA nonsignificant result was obtained from the microbiome diversity comparison among the different groups. However, we demonstrated that the OC group had a greater abundance of Lactobacillus and that the UM group had a lower abundance of Atopobium, which might contribute to the occurrence of diseases, providing new clues for preventive measures.